Dia de desafio: plano de aplicação de narrativa transmídia para o exército brasileiro - Dias, Leciane Moreira (2021)
The rapid development of information technologies has changed content comsuption on digital platforms. The user spends his/her time on different apps and websites and gets used to navigating through a variety of products offered by the cyberspace. That new dynamics has placed the transmedia storytelling as a possible communication strategy in order to catch the user’s attention and lead him to effectively consume the story. This research aims to approach the basics of transmedia storytelling and, while addressing some writters such as Jenkins (2009), Evans (2011), Pratten (2015) and Scolari (2016), to set up grounds for the creation of multiplatform storytelling for the Brazilian Army. This study makes use of bibliographic research in some fields including Communication, Cyberculture and Narratology in order to develop a plan for implementing a narrative that has a reality show as its key product. The web series Dia de Desafio (Challenge Day, in English) is transmedia storytelling since it expands the story to other platforms such as Facebook, Instagram and LinkedIn and produces contents tailored to sites and podcasts. By considering communication as something complex and recognizing the receiver as a social individual, it was decided to involve digital influencers referred to in this research as current new opinion leaders. For selecting profiles, selection criteria were established based on Karhawi (2021). From a faithful recording of the actions, Challenge Day aims to involve the audience in the characters’ story, hardships and achievements by means of a serial multiplatform storytelling. The implementation plan includes the following documents: proposition; single sheet; transmedia production bible; diagram of the user journey; list of selected influencer; step outline; and delivery plan.